Persepsi Pustakawan Pada Fungsi Hubungan Masyarakat (Humas) Di Perpustakaan Universitas Negeri Padang - Lizasri, Hanifa; Marlini, Marlini (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
Introduction. Public relations is an important service in the library, public relations functions as the delivery of information to users. This study aims to see the perceptions of librarians' perceptions in implementing the public relations function at the Padang State University Library. The specific objectives of this study are; (1) to see the perceptions of librarians in serving library users, (2) to be alert to foster trust from library users to librarians, (3) to see librarians in serving library users, (4) to see how to start and stop librarian communication with library, (5) to see how librarians notify library users if any. new collection, (6) to see the service implementation. public relations by librarians for library users. Data Collection Medhod. This research uses a qualitative method with a descriptive approach. Data collection was carried out by direct research into the library who conducted an interview with one of the librarians in the field of circulation services at the Library of Padang State University. Result And Discussions. Based on the results of research conducted, the results show that public relations services at the Padang State University Library in conveying information to users are based on user needs. The inability of users to find information is the librarian's job to find the information needed and convey information related to new collections that exist in the library to the library users. Conclusions. The research was conducted using qualitative methods to obtain information related to the perception and implementation of public relations at the Padang State University Library. Keyword: Public relations library, public relations service.